ANALOGUE MODELS OF OROGENIC WEDGES CONTROLLED BY EROSION - Persson K.S.; Sokoutis D. (My University, 2002)
Indentation in the upper brittle crust where one plate is stiffer than the other produces vertical extrusion of a doubly vergent orogenic wedge. Sandbox models of this process show that erosion with or without deposition of the eroded material onto one or both margins significantly changes the internal patterns of orogenic shear and compaction within the orogens. Erosion decreases the vertical stress and changes the criticality of the orogenic wedge, whereas redeposition increases the vertical stress on its margins.Effective indenters of accreted sand, which develop in models without erosion if the rigid indenter face dip is 75° (e.g., >45°) or =<15 are strongly affected by erosion. Rapid erosion favors thrusting over compaction and decreases both the size and the relevance of the effective indenters. Redeposition of eroded material on the margins also expands the lifetime of the active shear as the additional load delays initiation of underlying new shears.
Keywords: EROSION; OROGENIC WEDGES; SANDBOX MODELLING; DEPOSITION; INDENTER